Human granulocyte colony stimulating factor (hG-CSF): cloning, overexpression, purification and characterization - Vanz, Ana L. S.; Renard, Gaby; Palma, Mario Sergio [UNESP]; Chies, Jocelei M.; Dalmora, Sergio L.; Basso, Luiz A.; Santos, Diogenes S. (Biomed Central Ltd., 2008)
Background: Biopharmaceutical drugs are mainly recombinant proteins produced by biotechnological tools. The patents of many biopharmaceuticals have expired, and biosimilars are thus currently being developed. Human granulocyte colony stimulating factor (hG-CSF) is a hematopoietic cytokine that acts on cells of the neutrophil lineage causing proliferation and differentiation of committed precursor cells and activation of mature neutrophils. Recombinant hG-CSF has been produced in genetically engineered Escherichia coli ( Filgrastim) and successfully used to treat cancer patients suffering from chemotherapy-induced neutropenia. Filgrastim is a 175 amino acid protein, containing an extra N-terminal methionine, which is needed for expression in E. coli. Here we describe a simple and low-cost process that is amenable to scaling-up for the production and purification of homogeneous and active recombinant hG-CSF expressed in E. coli cells.Results: Here we describe cloning of the human granulocyte colony-stimulating factor coding DNA sequence, protein expression in E. coli BL21(DE3) host cells in the absence of isopropyl-beta-D-thiogalactopyranoside ( IPTG) induction, efficient isolation and solubilization of inclusion bodies by a multi-step washing procedure, and a purification protocol using a single cationic exchange column. Characterization of homogeneous rhG-CSF by size exclusion and reverse phase chromatography showed similar yields to the standard. The immunoassay and N-terminal sequencing confirmed the identity of rhG-CSF. The biological activity assay, in vivo, showed an equivalent biological effect (109.4%) to the standard reference rhG-CSF. The homogeneous rhG-CSF protein yield was 3.2 mg of bioactive protein per liter of cell culture.Conclusion: The recombinant protein expression in the absence of IPTG induction is advantageous since cost is reduced, and the protein purification protocol using a single chromatographic step should reduce cost even further for large scale production. The physicochemical, immunological and biological analyses showed that this protocol can be useful to develop therapeutic bioproducts. In summary, the combination of different experimental strategies presented here allowed an efficient and cost-effective protocol for rhG-CSF production. These data may be of interest to biopharmaceutical companies interested in developing biosimilars and healthcare community.